2019
DOI: 10.1088/1555-6611/aaf639
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of a weak probe in singly charged n-doped quantum dots in the Voigt geometry

Abstract: We analyze the absorption of a weak probe field in singly charged n-doped quantum dots in the presence of an external magnetic field in the Voigt geometry. The dots are modeled as double lambda systems. A laser field pumps two of the four active transitions while a probe field is applied along the two undriven transitions. It is shown that for both on resonance and out of resonance driving gain (without inversion) is obtained at two sidebands of the dressed QDs. We found that the peak value of gain can be maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…Beyond this interval, both C and B remain positive, leading to (47) having no physically meaningful solution, resulting in m being equal to zero. It can be demonstrated that within the interval p 1 < p < p 2 , the solution m ≠ 0 is stable, while for values of p below p 1 and above p 2 , the solution of m = 0 will be stable [79][80][81][82][83][84][85][86][87]. This corresponds to the lasing regime, where p 1 can be identified as the lasing threshold.…”
Section: Ammentioning
confidence: 98%
“…Beyond this interval, both C and B remain positive, leading to (47) having no physically meaningful solution, resulting in m being equal to zero. It can be demonstrated that within the interval p 1 < p < p 2 , the solution m ≠ 0 is stable, while for values of p below p 1 and above p 2 , the solution of m = 0 will be stable [79][80][81][82][83][84][85][86][87]. This corresponds to the lasing regime, where p 1 can be identified as the lasing threshold.…”
Section: Ammentioning
confidence: 98%